Pengaruh Kepemimpinan Politik Terhadap Kinerja Karyawan/Kedisiplinan Karyawan - Aprinawati Aprinawati; Luhut Manurung; Nisa Artia Nababan; Rosana Vanessa Triyulina Girsang; Tamara Meilita Marpaung; Imamul Khaira (Departement of Mathematics Education, 2024)
This article discusses the influence of political leadership style on employee performance and discipline in state-owned companies in Indonesia. The research method used is qualitative with secondary data analysis. The results show that fair and thoughtful political leadership contributes positively to employee discipline, while overly dominant leadership can decrease motivation and discipline. Factors such as organizational culture, education level, and employee involvement in decision-making also influence this relationship. Transparent and fair politics can increase discipline, while poorly managed politics can lead to dissatisfaction. The article also emphasizes the importance of further research to understand the relationship between political leadership and employee discipline and develop strategies to reduce the negative impact on employee productivity and well-being